POLITIK BHINNEKA TUNGGAL IKA DALAM KERAGAMAN BUDAYA INDONESIA - Abdullah, Irwan (Jurnal Masyarakat dan Budaya, 2003)
This article discusses the experience of maintaining a plural culture in Indonesia which has led to the birth of various resistance and conflicts in society. This maintaining process takes the form of cultural politics. While on one side this process has been a unifying one in developing national identity based on the principle of unity and on the other side it has limited the potential for political freedom in the expression of various local cultures. This practice of cultural politics is manifested in three forms: the denial of diverse cultural status; political uniformity which is oriented to the forming of similar points of view; and the creation of a gap between the power relationships of ethnicity in the form of controlling resources. These three processes have resulted in the creation of strict borders between ethnic groups, religion, races and between groups which have further led to various conflicts in society. This experience of maintaining cultural diversity has shown the danger in inaccurately conceptualizing the terms “one”, “oneness” and “unity” because the existence and power of various cultures has been misinterpreted.